Pengaruh Moralitas Individu, Keadilan Organisasi, dan Pengendalian Internal terhadap Kecenderungan Kecurangan Akuntansi pada SKPD Kabupaten Buleleng - Pratiwi, Luh Putu Ratna; Werastuti, Desak Nyoman Sri (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
The purpose of this study was to partially determine the effect of individual morality, organizational justice, and internal control on the tendency of accounting fraud at SKPD Buleleng Regency. The method used in this research is quantitative method. Collecting data using a Likert scale questionnaire. The population used was all SKPDs in Buleleng Regency totaling 39 SKPDs. The sample in this study used a saturated sample technique using 146 employees who were in the financial department of the SKPD Buleleng Regency as respondents. This study uses the SPSS 16 application to assist the author in processing data. The data analysis methods and techniques used are instrument test, descriptive statistics, classical assumption test, and multiple linear analysis.The result of this research is that individual morality has no effect on the tendency of accounting fraud. Organizational justice has a negative effect on the tendency of accounting fraud. Internal control has a negative effect on the tendency of accounting fraud.Â